Из дневников Константина Локса - Sergeeva-Kljatis (Hrsg.), Anna (Wiener Slawistischer Almanach, 2024)
The publication introduces the reader to the diaries of Konstantin Loks (1889–1956), a translator, literary critic, and fellow student and acquaintance of Boris Pasternak. Loks commenced the writing of his diaries at a very young age; from his college years onwards, they were supplemented by short remembrances about events both past and present, in his current social circle. Over time, the creation of diaries and fragmentary memoirs became a natural way of (self-)reflection for Loks. He did not limit himself to brief mentions of present goings-on—instead, his writings partially unfold into detailed accounts about people and the present, into observations on literature, or philosophic deliberations. The published fragments represent a thematic selection from one of Loks’s diaries in its entirety (i.e., one notebook), dated between 1924 and 1950. Beyond mere descriptive insights, this publication also provides an overview of the material available in abundance in Loks’ archive at the Russian State Library’s Department of Manuscripts.